Cross-sectional stress distribution in AlxGa1-xN heterostructure on Si(111) substrate characterized by ion beam layer removal method and precession electron diffraction. (15th September 2016) - Reisinger, M.; Zalesak, J.; Daniel, R.; Tomberger, M.; Weiss, J.K.; Darbal, A.D.; Petrenec, M.; Zechner, J.; Daumiller, I.; Ecker, W.; Sartory, B.; Keckes, J.
Abstract: A residual stress depth gradient is characterized in a 1.8 μm thick AlN/Al0.25 Ga0.75 N/GaN/Al0.22 Ga0.78 N heteroepitaxial structure grown using metallic-organic chemical vapour deposition on Si(111) substrate. The cross-sectional stress profile is evaluated with a step of 100 nm using ion beam layer removal (ILR) method based (i) on a sequential focused ion beam milling of a microcantilever, (ii) on an evaluation of a cantilever bending after every milling step and (iii) on a stress profile recalculation using finite element simulation. The profile shows tensile stress of ~ 1.5 GPa in AlN nucleation layer, stress changing from compressive to tensile in Al0.25 Ga0.75 N and GaN sublayers and relatively small stresses below 100 MPa in the top Al0.22 Ga0.72 N sublayer. The stress profile is qualitatively correlated with the results from precession electron diffraction which indicates approximately the same stress behavior. The cross-sectional stress magnitude and variation are interpreted by the mismatches of lattice constants and coefficients of thermal expansion as well as by growth mode changes during Al0.25 Ga0.75 N and GaN sublayer formation. The approach demonstrates the possibility to resolve nanoscale variation of residual stresses in heteroepitaxial structures using ILR method. Graphical abstract: Highlights: Ion Beam Layer Removal (ILR) characterization of stresses in heteroepitaxial thin film Precession electron diffraction characterization of Alx Ga1-x N heterostructure Nonlinear stress gradient in Alx Ga1-x N heterostructure